Development and characterization of biocompatible isotropic and anisotropic oil-in-water colloidal dispersions as a new delivery system for methyl dihydrojasmonate antitumor drug - Rolfsen Ferreira da Silva, Gisela Bevilacqua [UNESP]; Scarpa, Maria Virginia [UNESP]; Rossanezi, Gustavo [UNESP]; Tabosa do Egito, Eryvaldo Socrates; Oliveira, Anselmo Gomes de [UNESP] (Dove Medical Press Ltd, 2014)
Microemulsions (MEs) are colloidal systems that can be used for drug-delivery and drug-targeting purposes. These systems are able to incorporate drugs modifying bioavailability and stability and reducing toxic effects. The jasmonate compounds belong to a group of plant stress hormones, and the jasmonic acid and its methyl ester derivative have been described as having anticancer activity. However, these compounds are very poorly water-soluble, not allowing administration by an intravenous route without an efficient nanostructured carrier system. In this work, biocompatible MEs of appropriate diameter size for intravenous route administration, loaded and unloaded with methyl dihydrojasmonate (MJ), were developed and described in a pseudo-ternary phase diagram. The compositions of the MEs were carefully selected from their own regions in the pseudo-ternary phase diagram. The formulations were analyzed by light scattering, polarized light microscopy, and X-ray diffraction. Also, a study on rheological profile was performed. The results showed that the droplet size decreased with both MJ incorporation and oil phase/surfactant ratio. All compositions of the studied MEs showed rheological behavior of pseudoplastic fluid and amorphous structures. In the absence of MJ, most of the studied MEs had thixotropic characteristics, which became antithixotropic in the presence of the drug. Almost all MJ-unloaded MEs presented anisotropic characteristics, but some formulations became isotropic, especially in the presence of MJ. The results of this study support the conclusion that the studied system represents a promising vehicle for in vivo administration of the MJ antitumor drug.
Keywords: methyl dihydrojasmonate; anticancer drug; biocompatible microemulsions; pseudo-ternary phase diagram; microemulsion characterization